Understanding the Ùrhòb ò Tonal Structure through Constraint-Based Framework. - Chukwuemeka Utulu, Don; Ajiboye, Emuobonuvie Maria; Eloho Edojaimoni, Irene (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2023)
Ùrhòb ò is a southwest Edoid language spoken in southern Nigeria. Its tonal patterns have been studied, but from a descriptive perspective, which, from a theoretical standpoint, potentially limits the understanding that tonal deviations from underlying forms are essentially due to resolutions of conflicts between some competing constraints. This study adopts the Optimality Theory (OT) to reveal the competing universal constraints: IDENT-T, MAX-T; NoFUSION; LINEARITY; DISASSOC; ALIGN-R CONTOUR; OCP; SPECIFY-T; *FLOAT; and NoCONTOUR. The study shows that these constraints crucially govern the Urhobo tonal patterns such as (i) downstep; (ii) single multiply-linked high (H) tone; (iii) single multiply-linked low (L) tone; (iv) boundary H.H and L.L tones fusion; (v); H-tone preservation; (vi) LH-tone preservation; (vii) floating H tone; and, (viii) final HL contour tone. Moreover, it highlights two Ùrhòb ò-specific tonal alternations listed in (v) and (vi), which exhibit preservation of H and LH tones at the expense of L tone, post-lexically. Consequently, it proposes four markedness constraints NoH.L-T, NoL.H-T, NoH.LH-T, and NoL. to explain the preservation effects. Our findings support phonologists' view that, crosslinguistically, universal (and language-specific) constraints are those that motivate tonal deviations from input forms in tone languages, and that minimally marked tonal outputs are the result of markedness dominance over faithfulness.